Successful T-cell–depleted Haploidentical Hematopoietic Stem Cell Transplantation in a Child With Dyskeratosis Congenita After a Fludarabine-based Conditioning Regimen. Issue 4 (May 2015) - Algeri, Mattia; Comoli, Patrizia; Strocchio, Luisa; Perotti, Cesare; Corbella, Franco; Del Fante, Claudia; Baio, Ambrogia; Giorgiani, Giovanna; Gurrado, Antonella; Accornero, Elisa; Cugno, Chiara; Pession, Andrea; et al.
<x xml:space="preserve">Abstract</x> Allogeneic hematopoietic stem cell transplantation (HSCT) is the only cure for marrow failure associated with dyskeratosis congenita (DC). Data on transplants from alternative donors are limited. We describe a boy with DC and severe aplastic anemia who underwent haploidentical T-cell depleted HSCT using a reduced-intensity conditioning regimen. He underwent engraftment without toxicity or GVHD. His posttransplant course was complicated by EBV reactivation, treated with rituximab and EBV-specific T lymphocytes. After 26 months, he is in complete chimerism, with normal blood count and no sign of GVHD or pulmonary dysfunction. To the best of our knowledge, this is the first report of DC successfully treated with allogeneic HSCT from a haploidentical family donor.